Material Culture in Cina Benteng Marriage Tradition: An Ethnography Studies - Sonya Ayu Kumala (ICHELSS: International Conference on Humanities, Education, Law, and Social Sciences, 2021)
Among all Chinese in Indonesia, Cina Benteng in Tangerang has its own uniqueness. Being called as Cina Benteng or "Ciben" because they lived in Colonial fortress and doing farming activities to supply food for Colonial. Their black skin, slanted eyes, having prayer ash table at their home, and mostly on medium-low economic and social level. Nowadays, Cina Benteng tradition’s is still hold and preserved. Its marriage tradition that is being called as Cio Tao rituals. This tradition is not only about material culture but also as a mean of historical and cultural memories in wider context. Marriage tradition in this writing will be regarded as a text that being functioned as the active agent in socio-cultural process (Auslander, 2005). The main argument of this writing is “How do material culture in Cina Benteng marriage tradition reflect collective memories of historical, cultural, and identity through its meaning”. This is an ethnography research that will use visual documentations and interviews. This writing uses qualitative approach and utilizes ethnography, archeology, and semiotics studies. The result of this writing shows, marriage tradition of Cina Benteng is an artifact that contains tangible and intangible meaning. These meaning are still relevant to modern life. It also highlighted that Cina Benteng culture are able to adapt and acculturate to other culture in its context. Keywords: Ethnography, Artifact, Material Culture, Cina Benteng